Bone regeneration in alimentary osteoporosis (an experimental study) - Dedukh, Ninel; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
A morphological study of the effect produced by a low-calcium diet on the course of the reparative regeneration in an injury of the distal femoral metaphysis was made in an experiment on 140 white rats. The inflammatory-proliferative stage of osteorepair in animals with alimentary osteoporosis at the area of the defect developed a low functional activity of macrophages, as well as a smaller number of macrophages, tissue basophiles, and fibroblasts versus the control group. Also observed was some deceleration in the rate of catabolism of inflammation products and the process of cell differentiation of the fibroblastic and osteoblastic differon at early stages, thereby causing a delay in the reorganization of the regenerate tissues, a later formation of the osteoid, bone trabeculae and restoration of the cortical bone at subsequent stages.